(untitled) (Vietnam Journal of Community Medicine, 2025)
Objectives: Assessing the reliability of the scale using Cronbach’s Alpha coefficient and evaluating the factors influencing the engagement with retail businesses in the healthcare sector among sales staff in Can Tho city during the period 2024-2025. Materials and methods: A cross-sectional descriptive study was conducted using direct interviews and surveys via a link to a form or QR code, involving 449 sales staff currently working at healthcare-related business establishments across 9 districts in Can Tho city in 2025. Results: The reliability analysis results show that all 8 components have high Cronbach’s Alpha coefficients (ranging from 0.909 to 0.972), confirming the strong internal consistency of the measurement scales. The component “career development orientation” recorded the highest reliability (Cronbach’s Alpha = 0.972). All observed variables have item-total correlations greater than 0.7, and the Cronbach’s Alpha if item deleted is lower than the overall Alpha, so all items were retained. The six factors - human resource policies, career development orientation, promotion opportunities, compensation and rewards, workplace environment, and workplace relationships - all have a statistically significant impact on the engagement of sales staff in the healthcare sector (sig < 0.001). Conclusions: Studies have shown that factors such as human resource policies, career development orientation, promotion opportunities, compensation and rewards, workplace environment, and interpersonal relationships at work have a positive impact on employee engagement.